Pengaruh Customer Experience dan Switching Barriers Terhadap Keputusan Pembelian Kembali Melalui Kepuasan Konsumen pada UMKM Ritel - Feti Fatimah; Wenny Murtalining Tyas (Relasi : Jurnal Ekonomi, 2024)
Retail growth increases competition among retailers. However, in the intense competition, not all retailers are able to survive and thrive. The purpose of this study was to examine the effect of customer experience and switching barriers on repurchase decisions through satisfaction in Retail SMEs. The sample criteria are people who have bought from MSME Retail in Balung District Jember Regency , which sells daily necessities with the concept of a mini-market shop. The sample technique used is Accidental Sampling. The number of samples is 10 x 10 = 100 respondents. The analysis technique used in this study is Structural Equation Modeling (SEM) using the AMOS program version 23.0. The results of the study are First, customer experience has a positive and significant effect on consumer satisfaction at Retail MSMEs. Second, switching barriers have a positive and significant effect on consumer satisfaction in retail SMEs. Third, customer experience has a positive but not significant effect on repurchasing decisions at Retail MSMEs. Fourth, switching barriers have a positive and significant effect on repurchasing decisions in Retail SMEs. Fifth, consumer satisfaction has a positive and significant effect on repurchasing decisions at Retail MSMEs